TIME DEPENDENCE OF THE e− FLUX MEASURED BY PAMELA DURING THE 2006 JULY-2009 DECEMBER SOLAR MINIMUM - Adriani, O.; Barbarino, G. C.; Bazilevskaya, G. A.; Bellotti, R.; Boezio, M.; Bogomolov, E. A.; Bongi, M.; Bonvicini, V.; Bottai, S.; Bruno, A.; Cafagna, F.; Campana, D.; et al. (The Astrophysical journal, 2015)
ABSTRACT Precision measurements of the electron component of cosmic radiation provide important information about the origin and propagation of cosmic rays in the Galaxy not accessible from the study of cosmic-ray nuclear components due to their differing diffusion and energy-loss processes. However, when measured near Earth, the effects of propagation and modulation of Galactic cosmic rays in the heliosphere, particularly significant for energies up to at least 30 GeV, must be properly taken into account. In this paper the electron (e−) spectra measured by the Payload for Antimatter Matter Exploration and Light-nuclei Astrophysics down to 70 MeV from 2006 July to 2009 December over six-month time intervals are presented. Fluxes are compared with a state-of-the-art three-dimensional model of solar modulation that reproduces the observations remarkably well.